Verifikasi Identitas Biologis Menjelang Perkawinan dalam Perspektif Fikih - Alimin Mesra (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: Biological identity verification before marriage from a fiqh standpoint. This article treats falsifying biological identity for marriage as an important phenomenon that should be responded to academically. By way of analyzing discourse concerning this subject, this article reveals that weaknesses in how civil law and citizenry are administrated, if not fixed, will give rise to more such cases of it. On the other hand, the theory that love is the biggest motivation for falsifying biological identity is taken into account to clarify why this violation occurs. The conclusion reached in this article is to accommodate for the capacity to verify biological identity—when deemed necessary—before marriage. The author reinforces this idea by drawing upon several hadiths, applying al-maqâshid al-syâri‘ah theory, as well as calling to expand classical fiqh to the context of solving this contemporary problem.Keywords: biological identity, verification, contemporary problem, classical fiqh, contextualisationAbstrak: Verifikasi Identitas Biologis Menjelang Perkawinan dalam Perspektif Fikih. Artikel ini meletakkan fakta pemalsuan identitas biologis dalam perkawinan sebagai fenomena yang penting direspons secara akademis. Melalui analisis wacana atas berita yang terkait, tulisan ini menyingkap bahwa ada sejumlah kelemahan pada sistem administrasi keperdataan dan kependudukan yang jika tidak dibenahi akan melahirkan kasus-kasus serupa. Di sisi lain, teori bahwa cinta adalah motivasi terbesar untuk melakukan sesuatu dimanfaatkan untuk menjelaskan mengapa pelanggaran itu dilakukan. Kesimpulan yang direkomendasikan adalah mengakomodasi kebolehan melakukan verifikasi identitas biologis—jika dianggap perlu—sebelum perkawinan. Penulis menguatkan gagasan ini dengan melakukan kontekstualisasi atas beberapa hadis, penerapan teori maqâshid al-syarî’ah serta ajakan untuk mengembangkan fikih klasik dalam rangka mengatasi problematika kontemporer.Kata Kunci: verifikasi, identitas biologis, problema kontemporer, fikih klasik, kontekstualisasiDOI: 10.15408/ajis.v12i1.963